2013
DOI: 10.1073/pnas.1313480110
|View full text |Cite
|
Sign up to set email alerts
|

Topology of viral evolution

Abstract: The tree structure is currently the accepted paradigm to represent evolutionary relationships between organisms, species or other taxa. However, horizontal, or reticulate, genomic exchanges are pervasive in nature and confound characterization of phylogenetic trees. Drawing from algebraic topology, we present a unique evolutionary framework that comprehensively captures both clonal and reticulate evolution. We show that whereas clonal evolution can be summarized as a tree, reticulate evolution exhibits nontriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
189
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(198 citation statements)
references
References 44 publications
2
189
0
1
Order By: Relevance
“…By Proposition 1. (c), u and v cannot both be stable on l 1 . If u is stable on l 1 and v is stable on l 2 , by Proposition 1.…”
Section: The Algorithmmentioning
confidence: 96%
See 1 more Smart Citation
“…By Proposition 1. (c), u and v cannot both be stable on l 1 . If u is stable on l 1 and v is stable on l 2 , by Proposition 1.…”
Section: The Algorithmmentioning
confidence: 96%
“…Since v is a reticulation in P 1 , it is stable only on ℓ 1 is a subdivision of T in N ′′ . Therefore T is displayed in N ′′ .…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The later study was consistent with patterns found in laboratory-based approaches and employed a combination of phylogeny and population genetics techniques to quantify segment linkage. A novel approach, which examined the underlying topology of phylogenetic trees to infer reassortment events, found frequent linkage between genes of the polymerase complex in avian strains [33 ].…”
Section: General Viral Reassortmentmentioning
confidence: 99%
“…The most important tool of TDA is the persistent homology method [12,13], which is proven as useful in many real-world applications. The abundance of applications covers a broad range of phenomena in biological and medical science, like breast cancer research [14], brain science [15][16][17][18][19][20][21], biomolecules [22][23][24], evolution [25] and bacteria [26], followed by the applications in sensor networks [27,28], signal analysis [29], image processing [30], musical data [31], text mining [32], phase space reconstruction of dynamical systems [33,34], as well as complex networks related to either dynamics taking place on networks [35] or structural properties [36,37].…”
Section: Introductionmentioning
confidence: 99%